The Effects of the Workplace Environment on the Mental and Emotional Health of Healthcare Workers - Hakami, Mohammed Awaji; Tohari, Fatimah Mousa Ahmed; alshamrani, Abdullah mansour; Alshammari , Abdullah Abdulaziz Atnan; Albalawi, Abdulbari Atallah ibrahim; Alrasheed, Abdulaziz Abdullah Mohammed; hassani , Aeshah abdullah; ALANAZI, KHALAF AMASH; Alsaeed, Narjis Hassan; Al-Azmi , Souad; Abid , Hisham Mohammed; Alkhayat, Haitham Hassan (Journal of Ecohumanism, 2024)
Background: Healthcare workers are often exposed to high levels of stress due to the demanding nature of their jobs. Prolonged exposure to stress can negatively affect both physical and mental health, leading to burnout and decreased work efficiency. The work environment in healthcare settings, along with coping strategies, plays a crucial role in determining the emotional well-being of healthcare professionals. This study investigates the impact of healthcare workers' job environment on their emotional health and the coping strategies they employ. Methods: This study was conducted with a sample of 400 healthcare professionals . Participants, aged 21 to 58, were selected through stratified random sampling. A standardized instrument, the Coping Strategies for Stressful Events (CSSE), was used to assess the coping strategies employed by participants. Demographic data and healthcare roles were collected through a separate questionnaire. The data were analyzed using SPSS v.16, with t-tests, ANOVA, and linear regression to examine relationships between coping strategies, work environment, and mental health outcomes. Results: The study found significant differences in coping strategies between male and female healthcare professionals, with females tending to use more emotion-centered strategies like wishful thinking and seeking divine support. Health status, family status, and years of employment also influenced the coping strategies used. Healthcare workers with better health were more likely to use positive strategies, while those with fewer years of experience employed problem-solving strategies more frequently. A positive correlation was found between the use of problem-solving and positive reassessment strategies and better emotional well-being. Conclusion: The emotional health of healthcare professionals is significantly influenced by both their work environment and coping strategies. Positive coping strategies, particularly problem-solving and positive reassessment, contribute to better mental and emotional well-being. Factors such as health status, family situation, and years of experience also play key roles in determining the coping strategies employed. These findings highlight the importance of creating supportive work environments and promoting effective coping strategies to improve healthcare workers' emotional health and job satisfaction.